Safety and efficacy of corticosteroids in ARDS patients: a systematic review and meta-analysis of RCT data - Xinyan Chang; Shaojun Li; Yueqiang Fu; Hongxing Dang; Chengjun Liu (Respiratory Research, 2022)
Abstract Purpose Acute respiratory distress syndrome (ARDS) is an acute and critical disease among children and adults, and previous studies have shown that the administration of corticosteroids remains controversial. Therefore, a meta-analysis of randomized controlled trials (RCTs) was performed to evaluate the safety and efficacy of corticosteroids. Methods The RCTs investigating the safety and efficacy of corticosteroids in ARDS were searched from electronic databases (Embase, Medline, and the Cochrane Central Register of Controlled Trials). The primary outcome was 28-day mortality. Heterogeneity was assessed using the Chi square test and I 2 with the inspection level of 0.1 and 50%, respectively. Results Fourteen RCTs (n = 1607) were included for analysis. Corticosteroids were found to reduce the risk of death in patients with ARDS (relative risk (RR) = 0.78, 95% confidence interval (CI): 0.70–0.87; P < 0.01). Moreover, no significant adverse events were observed, compared to placebo or standard support therapy. Further subgroup analysis showed that variables, such as adults (RR = 0.78; 95% CI: 0.70–0.88; P < 0.01), non-COVID-19 (RR = 0.71; 95% CI: 0.62–0.83; P < 0.01), methylprednisolone (RR = 0.70; 95% CI: 0.56–0.88; P < 0.01), and hydrocortisone (RR = 0.79; 95% CI: 0.63–0.98; P = 0.03) were associated with 28-day mortality among patients who used corticosteroids. However, no association was found, regarding children (RR = 0.21; 95% CI: 0.01–4.10; P = 0.30). Conclusion The use of corticosteroids is an effective approach to reduce the risk of death in ARDS patients. However, this effect is associated with age, non-COVID-19 diseases, and methylprednisolone and hydrocortisone use. Therefore, evidence suggests patients with age ≥ 18 years and non-COVID-19 should be encouraged during the corticosteroid treatment. However, due to substantial differences in the use of corticosteroids among these studies, questions still remain regarding the dosage, optimal corticosteroid agent, and treatment duration in patients with ARDS.